Pengaruh Religiusitas terhadap Keputusan Pembelian Obat Herbal dengan Mediasi Gaya Hidup Sehat pada Konsumen Muslim di Kota Kendari - Edwin Oza Pratama; La Ode Alimusa; Al Asy Ari Adnan Hakim (Universitas Muhammadiyah Surabaya, 2023)
Theoretically, religiosity plays an important role in shaping a Muslim's healthy lifestyle and has been shown to influence purchasing decisions for health products including herbal medicines. This study aims to examine the effect of religiosity on purchasing decisions of herbal medicines for Muslim consumers in Kendari City Southeast Sulawesi, either directly or through the mediation of a healthy lifestyle. This research is quantitative research using PLS-SEM analysis to answer the research hypothesis. This research was conducted on 100 herbal consumers in Kendari City through survey questionnaires. The results of this study show that there is a positive and significant influence between religiosity on herbal medicine purchasing decisions, and a healthy lifestyle has a mediating role between religiosity on herbal medicine purchasing decisions on Muslim consumers in Kendari City Southeast Sulawesi.